Droit du transport de passagers et responsabilité civile - Langer, Léhi (Université Jean Monnet, 2025)
À l'heure d'une mobilité toujours plus intense, le transport de passagers occupe une place essentielle dans nos sociétés. Son développement continu, porté par les progrès techniques, l'essor du tourisme et les politiques publiques, s'accompagne de nouveaux défis juridiques, en particulier en matière de responsabilité civile. Cette thèse interroge les transformations du droit de la responsabilité civile à la lumière des règles spécifiques au transport de passagers, dans un contexte marqué par une forte influence du droit européen et international.L'étude révèle un double mouvement : l'affirmation de droits autonomes pour les passagers d'une part, et la reconfiguration du rôle de la responsabilité civile d'autre part. Le contrat de transport, bien que central, cède partiellement sa place à des droits issus directement de normes européennes. Cette évolution complexifie la distinction entre responsabilité contractuelle et délictuelle, au profit de mécanismes hybrides de réparation et de garantie.Face à la diversité des sources et des régimes applicables selon les modes de transport, la cohérence du droit devient un enjeu majeur. La thèse propose une clarification des obligations du transporteur et une délimitation précise des notions clés telles que l'accident, le dommage corporel ou les circonstances extraordinaires. Elle appelle aussi à repenser certains fondements, notamment à l'aune des transports autonomes, des plateformes numériques et des défis posés par la multimodalité.En définitive, le droit du transport de passagers apparaît comme un champ d'expérimentation de la responsabilité civile contemporaine. Il invite à trouver un nouvel équilibre entre protection des passagers, efficacité du système et sécurité juridique des opérateurs. In an era of ever-increasing mobility, passenger transport plays a vital role in our societies. Its continuous development—driven by technological progress, the growth of tourism, and public policy—is accompanied by new legal challenges, particularly regarding civil liability. This thesis examines the evolution of civil liability in light of the specific rules governing passenger transport, within a context heavily influenced by European and international law.The study reveals a dual dynamic: on the one hand, the emergence of autonomous rights for passengers; on the other, a redefinition of the role of civil liability. While the transport contract remains central, it is increasingly complemented—if not partially replaced—by rights granted directly through European regulations. This shift complicates the traditional distinction between contractual and tortious liability, giving rise to hybrid mechanisms of reparation and protection.Given the diversity of sources and legal regimes across different transport modes, legal coherence becomes a major concern. The thesis proposes a clarification of the carrier's obligations and a precise delineation of key concepts such as "accident", "bodily harm", and "extraordinary circumstances". It also calls for a reconsideration of certain legal foundations, especially in the face of autonomous transport, digital platforms, and the challenges of multimodality.Ultimately, passenger transport law emerges as a testing ground for modern civil liability. It invites a new balance between passenger protection, system efficiency, and legal certainty for operators.
Issue: 2025UJMO0054
Keywords: Contract; Contrat; Droits; Liability; Passager; Passenger; Protection; Responsabilité; Rights; Transport; Transportation

Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimatın e-memnuniyet, e-sadakat ve ödeme isteği üzerine etkisi: Tüketicilere yönelik karma yöntem uygulaması - Teki̇n, Makber (Akdeniz Üniversitesi, 2025)
Dijitalleşmenin hız kazandığı ve tüketici davranışlarının dönüşüme uğradığı günümüz e-ticaret ortamında, özellikle Covid-19 pandemisi sonrası çevrimiçi alışverişin yaygınlaşması sürdürülebilir lojistik uygulamalarının önemini artırmıştır. Artan sipariş hacmi, çevresel etkiler, karbon salımı ve teslimat sürelerine ilişkin beklentiler; daha verimli, esnek ve çevre dostu teslimat çözümlerine olan ihtiyacı gündeme getirmiştir. Bu bağlamda ev dışında teslimat gibi alternatif lojistik hizmetler ile sosyal, çevresel ve ekonomik sürdürülebilirlik yaklaşımları, tüketici davranışlarını etkileme potansiyeli taşıyan önemli değişkenler olarak öne çıkmaktadır. Bu doğrultuda tezin amacı, sürdürülebilir tedarik zinciri uygulamaları ile ev dışında teslimat modellerinin, e-memnuniyet, e-sadakat ve ödeme isteği üzerindeki etkilerini tüketiciler üzerinden incelemektir. Araştırma, açıklayıcı sıralı karma yöntem stratejisi ile yürütülmüştür. İlk aşamada 300'ü aşkın tüketiciden anket yoluyla nicel veriler toplanmış, ardından ikinci aşamada 27 katılımcı ile yapılan yarı yapılandırılmış görüşmeler aracılığıyla nitel veriler elde edilmiştir. Nicel veriler yapısal eşitlik modellemesiyle, nitel veriler ise tematik analiz yöntemiyle değerlendirilmiştir. Bulgular, özellikle sosyal ve çevresel sürdürülebilirlik boyutlarının e-memnuniyet üzerinde ve ekonomik ve çevresel sürdürülebilirlik boyutlarının ise e-sadakat üzerinde anlamlı etkiler yarattığı yönündedir. Sürdürülebilirliğin üç boyutu da ödeme istekliliği üzerinde anlamlı ve pozitif bir etki yaratmamıştır. Ekonomik sürdürülebilirlik boyutu ise tüketiciler tarafından doğrudan algılanamadığı için memnuniyet üzerinde anlamlı bir etki göstermemiştir. Ev dışında teslimat uygulamalarının esneklik, zaman tasarrufu ve erişilebilirlik gibi avantajlar sunarak e-memnuniyeti ve ödeme isteğini artırdığını göstermektedir. Son olarak e-memnuniyetin, e-sadakati ve e-sadakatin, ödeme isteğini pozitif yönde anlamlı etkilediği sonucuna ulaşılmıştır. Bu tez, sürdürülebilir tedarik zinciri yönetimi, ev dışında teslimat ve e-ticarette tüketici memnuniyeti, tüketici sadakati ve ödeme isteğini bütüncül biçimde ele alan özgün bir model sunmaktadır. Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimat hizmetlerinin tüketici davranışları üzerindeki etkilerini açıklamak amacıyla Sosyal Kimlik Teorisi (SIT), Yeşil Tüketici Davranışı Yaklaşımı ve destekleyici olarak Yeniliğin Yayılımı Teorisi (YYT) çerçevesinde şekillenen kuramsal yapı, sürdürülebilir uygulamaların tüketicilerdeki karşılığını açıklamaya yardımcı olmuştur. Ayrıca bu çalışma, Türkiye örneğinde sürdürülebilir teslimat hizmetlerine yönelik farkındalık düzeyini ve bu hizmetlerin e-memnuniyet, e-sadakat ve ödeme davranışları üzerindeki etkilerini analiz ederek hem akademik literatüre hem de pratik lojistik ve pazarlama stratejilerine katkı sunması beklenmektedir. In today's rapidly evolving e-commerce landscape, shaped by accelerated digitalization and shifting consumer behaviors, the widespread adoption of online shopping - particularly in the aftermath of the Covid-19 pandemic - has amplified the significance of sustainable logistics practices. Increasing order volumes, environmental impacts, carbon emissions, and heightened expectations regarding delivery times have underscored the need for more efficient, flexible, and eco-friendly delivery solutions. In this context, out-of-home delivery services and the dimensions of social, environmental, and economic sustainability have emerged as key variables with the potential to influence consumer behavior. Accordingly, the purpose of this dissertation is to examine the effects of sustainable supply chain practices and out-of-home delivery models on e-satisfaction, e-loyalty, and willingness to pay, through the lens of consumer perceptions. The research adopts an explanatory sequential mixed-methods design. In the first phase, quantitative data were collected via a survey administered to over 300 consumers; in the second phase, qualitative data were obtained through semi-structured interviews conducted with 27 participants. The quantitative data were analyzed using structural equation modeling, while the qualitative data were evaluated through thematic analysis. The findings indicate that the social and environmental dimensions of sustainability have a significant impact on e-satisfaction, while the economic and environmental dimensions significantly influence e-loyalty. None of the three dimensions of sustainability were found to have a significant and positive effect on willingness to pay. The economic dimension of sustainability did not show a significant effect on satisfaction, likely because it is not directly perceived by consumers. Out-of-home delivery practices were found to enhance e-satisfaction and willingness to pay by offering advantages such as flexibility, time savings, and accessibility. Finally, the results revealed that e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty, in turn, significantly and positively affects willingness to pay. This study aims to develop an original and integrative model that examines sustainable supply chain management, out-of-home delivery, and key consumer outcomes in e-commerce, namely e-satisfaction, e-loyalty, and willingness to pay. Grounded in the Social Identity Theory (SIT), the Green Consumer Behavior Approach, and supported by the Diffusion of Innovations Theory (DOI), the proposed theoretical framework explains how sustainable supply chain practices and out-of-home delivery services shape consumer behavior. Moreover, by investigating the level of awareness of sustainable delivery services in the Turkish context and analyzing their effects on e-satisfaction, e-loyalty, and payment behavior, this research is expected to provide significant contributions to both academic literature and practical implications for logistics and marketing strategies.
Keywords: E-commerce; E-ticaret; Ev Dışı Teslimat; Green Consumer Behavior; Karma Yöntem; Mixed Methods; Out-of-Home Delivery; Sustainable Supply Chain Practices; Sürdürülebilir Tedarik Zinciri Uygulamaları; Yeşil Tüketici Davranışı

La Protection juridique des dossiers passagers - Nawaf Shathil, Shathil (Université Paris 1, 2024)
Les attentats du 11 septembre 2001 ont profondément bouleversé les sociétés occidentales. Le transport aérien international mais également plusieurs branches du droit, dont le droit pénal et le droit des libertés publiques, ont été affectés. Le droit américain a imposé aux compagnies aériennes la transmission des données personnelles des passagers aériens, appelées Passenger Name Record (PNR). Alors que les États-Unis exigent cette transmission pour des raisons de sécurité nationale, le droit européen privilégie la protection de la vie privée et des données personnelles. Bien que l'accord euro-américain et d'autres accords similaires, ainsi que la directive européenne sur les PNR, visent à encadrer les échanges de données, ils sont susceptibles de porter atteinte aux droits fondamentaux des passagers. Cet équilibre entre sécurité et droits individuels se heurte à une réalité juridique : une limitation des libertés au nom de la sécurité collective. Tandis que le Conseil et la Commission européenne prônent des mesures sécuritaires, le Parlement européen et la Cour de justice de l'Union européenne cherchent à préserver les libertés individuelles. De nouvelles menaces pèsent sur la protection juridique des dossiers passagers telles que la collecte massive de données et le profilage aux frontières. L'intervention croissante des acteurs privés, notamment dans les aéroports, affaiblit cette protection et la déterritorialisation des données accentue cette vulnérabilité. Les crises internationales, comme la pandémie du coronavirus, ont encore renforcé l'usage de ces données, compliquant leur encadrement juridique. The terrorist attacks of September 11, 2001, significantly disrupted Western societies. International transport law, along with areas of law such as criminal law and public freedoms, were profoundly affected. U.S. legislation imposed an obligation on airlines to transmit the personal data of air passengers, referred to as Passenger Name Record (PNR). While the U.S. requires this transmission for purposes of national security, European law prioritizes data protection. Despite the aim of the Euro-American agreement, other bilateral accords, and the European PNR Directive to regulate data exchanges, they pose a risk of infringing upon passengers' fundamental rights. This legal balance between security and individual rights reveals a tension: the restriction of civil liberties in the name of collective security. While the European Council and Commission endorse security-focused measures, the European Parliament and the Court of Justice of the European Union (CJEU) seek to uphold individual liberties. Emerging threats to the legal protection of passenger data include mass data collection and profiling at borders, which are at odds with privacy rights. The growing involvement of private actors, particularly in airports, further undermines this protection, while the de-territorialization of data exacerbates its vulnerability. Additionally, international crises such as the COVID-19 pandemic have led to an expanded use of passenger data, complicating its legal regulation and oversight.
Issue: 2024PA01D034
Keywords: Airport; Aéroport; Données des dossiers passagers; Droits fondamentaux; Etats-Unis; European Union; Individual rights; PNR; Protection; Protection de l'information (informatique); Sécurity; Sécurité collective; Terrorisme; Transport; Union européenne; United States

Les enjeux de la transition écologique dans le transport maritime : analyse et perspectives d'évolution du cadre juridique - Querel, Morgane (Nantes Université, 2024)
Le transport maritime est une activité essentielle pour le fonctionnement des sociétés modernes. Il a des fonctions économique et sociale incontestables. Elles ne s’arrêtent pas au navire, objet principal du transport maritime. De nombreux acteurs terrestres, nécessaires à sa construction, sa vie opérationnelle puis à son démantèlement, vivent aussi pour et grâce à cette activité. Tous ces éléments en font une activité d’importance mondiale. Dans un contexte de prise de conscience de l’impact des activités humaines sur l’environnement, le transport maritime peut être « pointé du doigt » pour la pollution marine et atmosphérique qu’il génère. C’est pourquoi, il est aujourd’hui indispensable de travailler sur une transition de cette activité pour la rendre plus respectueuse de l’environnement. Toutefois, cette transition comporte plusieurs enjeux. En effet, de nombreux obstacles techniques et économiques, en plus de l’importance de préserver le marché mondial du transport maritime, vont compliquer le travail pour réduire la pollution provenant des navires. C’est dans ce cadre que le droit maritime va intervenir. Il est adopté principalement, mais pas uniquement, au niveau international. Ce droit va inciter, ou obliger, selon les sujets, les acteurs du secteur à réduire leur empreinte environnementale. Il est produit principalement par l'Organisation Maritime Internationale (OMI) et porte majoritairement sur le navire. Dans son élaboration, il doit prendre en compte tous les enjeux liés à cette activité. Toutefois, en analysant certaines réglementations qui existent aujourd’hui, des lacunes apparaissent pour permettre la transition écologique du transport maritime. À l’inverse, d’autres réglementations ont fait leurs preuves dans la lutte contre un type de pollution. L’analyse de tous ces textes, mise en lumière avec des retours d’expériences régionales ou nationales, fait ressortir les éléments nécessaires pour construire un droit effectif et efficace, et ouvre des voies d’amélioration du droit maritime international.
Keywords: Bruit sous-marin; Droit maritime; Eaux de ballast; Ecological transition; Environment; Environnement; International Maritime Organization (IMO); Marée noire; Mer; Organisation Maritime Internationale (OMI); Pollution; Pollution atmosphérique; Pollution marine; Recyclage des navires; Transition écologique; Transports maritimes

Pazarlamacılık sözleşmesi - Kaya, Servecan (Üniversitesi Ankara, 2024)
Ticari hayatta duyulan ihtiyaç sonucu ortaya çıkmış sözleşmelerden birisi olan pazarlamacılık sözleşmesi, sıklıkla uygulanan sözleşmelerden olması ve hizmet sözleşmesinin özel bir türü olmasına karşın farklılaştığı hususların önemi sebebiyle kanun koyucu tarafından Türk Borçlar Kanunu içerisinde hizmet sözleşmesinden ayrı olarak düzenlenmiştir. Kanuni bir tanımının da bulunmasının etkisiyle tarafları ve unsurları rahatlıkla belirlenebilir mahiyettedir. Pazarlamacılık sözleşmesi unsurları; bağımlılık, süreklilik, iş yeri dışı faaliyet alanı ve ücret olan, rızai ve tam iki tarafa borç yükleyen bir isimli sözleşmedir. Pazarlamacılık sözleşmesinin taraflarından sözleşmeye de ismini vermiş olan pazarlamacı aynı zamanda bağımlı bir tacir yardımcısıdır. Bu bağlamda pazarlamacılık sözleşmesinin benzer olduğu birçok sözleşme bulunduğu gibi pazarlamacının da benzer olduğu birçok tacir yardımcısı bulunmaktadır, ancak her ikisinin de özüne inildiğinde benzer noktalardan ziyade diğerlerinden farklı karakteristik özellikleri bulunduğu rahatlıkla anlaşılacaktır. Tarafların hakları ve yükümlülükleri genel itibariyle pazarlamacılık sözleşmesinde birbirlerine karşılık gelmektedir, sözleşme böylece taraflar arasında kurulur, sürer ve sona erer. Pazarlamacılık sözleşmesinin sona ermesinde hizmet sözleşmesine ilişkin sona erme hallerinin söz konusu olduğu gibi kendine has sona erme halleri de söz konusudur. Her sözleşmede olduğu gibi sona erme halinde bunun da meydana getireceği sonuçlar taraflar özelinde kendisini gösterir. Ticaret hukuku ve borçlar hukuku özellikleri gösteren bir sözleşme olan pazarlamacılık sözleşmesi, özellikle belirli sektörlerde sıklıkla uygulanması, uyuşmazlıklara konu olması haricinde pazarlamacının sözleşmenin diğer tarafı olan işverene bağlı olarak faaliyet göstermesi sebebiyle de iş hukuku özelliği de gösteren bir sözleşmedir. Traveling salesman, which is one of the contracts that emerged as a result of a need in commercial life, has been arranged separately from the contract of service in the Turkish Code of Obligations, due to the importance of the matters that differentiate it, although it is one of the most frequently applied contracts and it is a special type of contract of service. With the effect of having a legal definition, its parties and facts can be easily identified. Traveling salesman is a consensual and bilateral contract with its elements which are dependency, continuity, non-operational field of business and fee. Traveling salesman as one of the parties of traveling salesman contract, who has given its name to the contract, is also a dependent tradesman assistant. In this context, as there are several contracts that traveling salesman is similar to, there are several tradesman assistants that traveling salesman is similar to, but when the essence of both is examined, it will be easily understood that they have various characteristics from the others. The rights and obligations of the parties generally correspond to each other in traveling salesman, so the contract is concluded, continued and terminated between the parties. In the termination of traveling salesman, there are specific termination cases as well as the termination cases related to contract of service. As with every contract, the consequences of termination in the event of termination will manifest themselves in particular to the parties. Traveling salesman is a contract that has the characteristics of commercial law and law of obligations, and also is a contract that has labor law characteristics, especially since it is frequently applied in certain sectors, is the subject of disputes, and because the traveling salesman operates under the employer, the other party of the contract.
Tez N°871625
Keywords: Code of Obligations; Commercial traveller; Contract; Traveling salesman

Hava Kargo Taşımacılığının Ülke Refahına Etkisi: OECD Ülke Analizi - Kelek, Bura Sabiha (İstanbul Ticaret Üniversitesi, 2024)
Bu çalışmanın amacı, ülkelerin rekabet güçleri açısından oldukça önemli olan lojistik performansları ile insani gelişmişlik düzeylerinin hava kargo ve küresel rekabet faktörlerinin nasıl ilişkili olduğunu ortaya koymaktır. Bunu ifade etmek için, 29 OECD (Ekonomik İş birliği ve Gelişme Teşkilatı) ülkesinin lojistik performanslarını hava taşımacılığının kargo göstergeleri ile ilişkilendirip ve sonuçları bahsi geçen ülkelerin insani gelişmişlik düzeyine etkisi açısından yorumlamaktır. Verilerin tüm ülkeler için eşit olmasına dikkat edilmiştir. Kullanılan puanlamaların zaman serisi 2010, 2012, 2014, 2016, 2018 yıllarını kapsamaktadır. Sonuçların analizi, kullanılan verilerin SPSS ile ortaya çıkarılarak oluşan yapısal eşitlik modellemesinin (YEM) üzerinden, çalışan ve çalışmayan regresyonların belirlenip ortaya hava taşımacılığı açısından etki eden verilerin bulgusuna erişmek ve yapılan analiz ile bu verilerin göstergesi ışığında hava lojistiği performansıyla ilişkili olup olmadığını göstermeye çalışılmaktadır. Çalışmada özellikle elde edilmek istenen bulgular bahsi geçen ülkelerin gayri safi milli hasıla ile kişi başına düşen milli gelirin hava taşımacılığının doğrudan veya dolaylı yoldan hem küresel rekabete olan etkisi hem de GSYİH’ye olan katkısıdır. Çalışma da lojistik kavramı ile birlikte ülkelerin ticaretleri ele alınarak dünya üzerindeki ticari üstünlüklerine değinilmiştir. Literatür araştırması, insani açıdan yetkin ülkelerin lojistik endüstrisine bakış açıları değerlendirilmiş ve lojistik alanındaki yükselişleri ile bağlantılı kalkınmasına işaret edilmiştir. Kullanılan veriler güvenilirlik açısından Dünya Bankası’ndan alınmış ve kullanılan endeksler çalışmanın kapsamında bulunan bütün parametreler ile analiz edilmiştir. Bunun sonucunda kurulan model de hava kargo taşımacılığının dolaylı olarak küresel rekabete etkisi ile Gayri Safi Yurtiçi Hasıla’ya ve aynı zamanda insani rekabet performanslarının lojistik performans endeksi ile anlamlı bir ilişki kurduğu ortaya çıkmıştır.
Keywords: Hava Kargo; Küresel Rekabet; Lojistik Performans; Lojistik Yönetimi; Milli Gelir

L'autonomisation des moyens de transport - Folliot, Océane (Université de Bordeaux, 2023)
Avec le développement de l'intelligence artificielle, sont apparus les robots intelligents, qui sont capables de simuler l'intelligence humaine dans des fonctions qui reviennent traditionnellement à l'homme. Ce phénomène de remplacement de l'homme par les machines autonomes s'observe notamment en matière de transports, avec l'émergence des véhicules autonomes, qui se distinguent des véhicules sans équipage. Ce processus d'autonomisation amorce une réflexion chez le juriste : qu'est ce que l'autonomie du moyen de transport ? Doit-on circonscrire cette autonomie ? Dans quelle mesure faut-il adapter le droit ?
Keywords: AI; Artificial Intelligence; Inteligência artificial; Intelligence Artificielle; Liability; Responsabilité; Robot; Systèmes de transport intelligent; Transport; Transport – Droit; Véhicules autonomes; Véhicules connectés

L'efficacité de l'expertise maritime amiable - Delaubier, Clara (Aix-Marseille Université, 2022)
La situation de l’expertise maritime amiable facultés peut être résumée par le constat suivant : bien qu’elle ne soit pas réglementée, elle est, dans le cadre des contrats d’assurances facultés, quasi-systématiquement prévue. La résolution de ce paradoxe réside dans l’efficacité de cette institution, forgée par sa pratique historique. Cette efficacité est fondée sur des caractéristiques, tenant d’abord à l’expert mais impactant également la réalisation de l’expertise. Sur la base des critères que doit présenter l’expert, à savoir la compétence et l’indépendance, les parties impliquées dans la négociation du contrat d’assurance facultés élaborent une liste d’experts agréés pour intervenir, en particulier, en cas de dommage. Néanmoins, ce choix ne lie pas les parties, les modalités devant présenter une certaine flexibilité afin de correspondre aux exigences du commerce international, dont le transport maritime est le vecteur principal. Par ailleurs, l’expertise doit être réalisée de manière méthodique et contradictoire afin de faire émerger la vérité factuelle du dommage et du sinistre et donc de pouvoir utilement remplir sa fonction principale, qui est probatoire. En tout état de cause, l’efficacité de l’expertise reste limitée, notamment au regard de la valeur probatoire que certaines juridictions françaises accordent au rapport d’expertise amiable, appelant des évolutions de l’expertise maritime ainsi qu’une amélioration des fondements de son efficience
Keywords: Adversary system; Assessment; Assurances facultés; Assurances maritimes; Cargo insurance; Commerce international; Competence; Compétence; Contradictory; Cotradictoire; Damage; Dommage; Efficacité; Efficiency; Evidence; Expert's survey; Expertise amiable; Expertises maritimes; Experts d'assurances; Facts; Fait; Independance; Indépendance; International trading; Loss; Probatory value; Proficiency; Self-Sufficiency; Sinistre; Survey report; Transports maritimes; Valeur probatoire

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

Multimodal taşıma operatörünün sorumluluğu - Alhan, Yunus (Akdeniz Üniversitesi, 2022)
Multimodal taşıma; multimodal taşıma sözleşmesine binaen multimodal taşıma operatörünün eşyaların bir yerden farklı yerdeki teslimat için belirlenmiş bir noktaya taşınmasını en az iki farklı taşıma türü ile gerçekleştirmeyi taahhüt ettiği bir taşımadır. Konteyner kullanımının yaygınlaşması, günümüzde uluslararası eşya taşımalarının birden fazla taşıma türü kullanılarak kapıdan kapıya şeklinde yapılmasına olanak sağlamıştır. Bu sayede multimodal taşıma tüm dünyada yaygın hale gelmiştir. Taşıma sektöründe sıklıkla kullanılan bu taşıma türünün hukuki açıdan izahı önem arz etmektedir. Bu sebeple, multimodal taşımanın tanımı ve unsurları ele alınmıştır. Bu taşımanın diğer taşıma türleri ile benzerlik ve farklıkları değerlendirilmiştir. Her bir taşıma türüne ilişkin konvansiyonlar, ülkelerin ulusal hukuk düzenlemeleri ve multimodal taşımaya ilişkin yeknesak kurallar oluşturma amacıyla getirilen düzenleme çalışmaları ve düzenlemeler göz önüne alındığında multimodal taşımaya hangi hukuk düzenlemelerinin uygulanacağını öngörmek zordur. Multimodal taşımalarda sorumluluğu yeknesaklaştırmak adına en önemli düzenlemeler 1975 ve 1992 tarihli Milletlerarası Ticaret Odası (ICC) Kuralları ve halen yürürlüğe girmemiş olan 1980 Tarihli Multimodal Taşıma Konvansiyonu (MTC), 2009 tarihinde imzaya açılan Eşyaların Tamamen veya Kısmen Deniz Yoluyla Uluslararası Taşınmasına İlişkin Konvansiyondur (Rotterdam Kuralları-RK). Bu düzenlemelerden esinlenilerek ortaya çıkmış çeşitli bölgesel düzenlemeler söz konusudur. Bunun yanı sıra multimodal taşımanın ülke sınırları içerisinde gerçekleşebilmesi sebebiyle bazı ülkeler bu konuyu düzenleyen kanunlar yapmışlardır. Türk Hukunda ise multimodal taşımaya ilk kez 6102 sayılı Türk Ticaret Kanunu'nda (TTK), 'Değişik Tür Araçlar İle Taşıma' başlığı altında yer verilmiştir. MTO'nun zıya, hasar ve geç teslime dayalı sözleşme kaynaklı sorumluluğu zarar yerinin belirlenebilir olup olmamasına göre farklı kurallara tabidir. Zarar yerinin belirlenmesi ve multimodal taşıma sözleşmesinin taraflarından birinin zararın hangi taşıma türünde oluştuğunu ispatlaması durumunda, multimodal taşıma birden fazla taşıma türünü içerdiğinden denizyolu, havayolu, karayolu, demiryolu ve ülke iç suyolu gibi her bir taşıma türünü ayrı ayrı düzenleyen ve her biri kendi sorumluluk rejimini içeren uluslararası unimodal (tekil) taşıma konvansiyonlarından usulüne göre yürürlüğe girmiş olanları öncelikli olmak üzere, ilgili taşıma türünü özel olarak düzenleyen kurallar uygulanacaktır. Zararın gerçekleştiği taşıma türünün tespit edilememesi durumunda genel hüküm olarak adlandırabileceğimiz TTK hükümleri uygulama alanı bulacaktır. Çalışmada, Türk Hukukunda MTO'nun sorumluluğu ilgili konvansiyonlar ve TTK ışığında ele alınmış, uygulanacak hükümler ortaya konmaya çalışılmıştır. Anahtar Kelimeler: Multimodal Taşıma, Multimodal Taşıma Sözleşmesi, Multimodal Taşıma Operatörü, Multimodal Taşıma Operatörünün Sorumluluğu. Multimodal transport is a carriage in which multimodal transport operator, who assumes the responsibility of performing the carriage under the multimodal transport contract, undertakes to perform the carriage of goods by at least two modes of transport from one place to another place designated for delivery. Widespread use of containers today allows international transport of goods to be in the form of door-to-door transport using more than one mode of transport. Thus, multimodal transport becomes more widespread all over the world. Explaining this mode of transport, which is frequently used in the transport industry, from the legal perspective is of high importance. Hence, in this study, the definition and elements of multimodal transport are studied. The similarities and differences of this mode of transport with other modes of transport are evaluated. Considering different conventions regulating each mode of transport, national transport legislations and regulations aimed at setting forth uniform provisions, it is clearly difficult to determine rules that are applicable for the multimodal transport contract. Major regulations to uniform the liability in multimodal carriages are the 1975 and 1992 International Chamber of Commerce Rules, the 1980 Multimodal Transport Convention (MTC) and the United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (Rotterdam Rules-RT), which was open for signature in 2009. There are also regional regulations inspired by these instruments. In addition, a number of countries enact laws regulating multimodal transport, as multimodal transport may be performed within national boundaries, and there are no uniform rules regulating it. In Turkish law, certain rules on multimodal transport in the Turkish Commercial Law (TTK) No.6102 under the heading of 'Carriage by Various Modes of Transport (Multimodal Transport)' were introduced. The MTO's contractual liability for loss of or damage to goods or delay in delivery is subject to different rules depending on whether the place of loss can be located. If the place of loss is located, and the leg of transport in which the loss occurs is proved by any party of the multimodal transport contract, as the transport involves more than one mode of transport, rules specifically regulating that mode of transport, in particular unimodal conventions, which duly entered into effect, individually governing each mode of transport such as sea, air, road, rail and inland waterway transports and having its own liability regime, will be applicable. If the mode of transport in which the loss occurs cannot be ascertained, TTK provisions, which we may call general rules, will be applicable. In the present study, we analyse the liability of MTO within the framework of relevant conventions and TTK and seek to reveal applicable provisions. Keywords: Multimodal Transport, Multimodal Transport Contract Multimodal Transport Operator, Liability of Multimodal Transport Operator
Keywords: Carrier's responsibility; Contract of carriage; Multimodal taşımacılık; Multimodal transport; Taşıma sorumluluğu; Taşıma sözleşmesi; Taşımacılık; Transportation; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Navlun sözleşmesinde gönderilenin sorumluluğu - Arslan, Zeynep (Kocaeli Üniversitesi, 2022)
Deniz ticaret hukukunda, varma limanında yükün teslimini talep eden kişi, gönderilen olarak tanımlanmaktadır. Gönderilen, navlun sözleşmesinin tarafı olan taşıtan olabileceği gibi sözleşme ilişkisi dışında üçüncü bir kişi de olabilir. Gönderilenin üçüncü kişi olması hâlinde navlun sözleşmesi üçüncü kişi yararına sözleşme olarak nitelendirilmektedir. Kanun koyucu, sözleşme ilişkisine taraf olmayan bu üçüncü kişi için de bir takım hak ve sorumluluklar getirmiştir. İşte bu çalışmanın konusunu üçüncü kişi sıfatını haiz gönderilenin navlun sözleşmesinden kaynaklanan sorumluluğu oluşturmaktadır. Sözleşmelerin nispiliği prensibi gereği kural olarak tarafların anlaşarak üçüncü kişiyi borç altına sokmaları mümkün değildir. Bununla birlikte üçüncü kişi gönderilenin hangi hallerde sorumlu olacağı TTK m. 1203'te düzenlenmiştir. Buna göre gönderilenin navlun sözleşmesi kapsamında sorumlu olması için ilk olarak eşyanın teslimini talep etmesi gerekmektedir. Eşyanın teslimini talep, üçüncü kişi lehine sözleşme teorisi açısından edimin kabulü olarak değerlendirilmekte ve haliyle gönderilenin borç altına girmesi tarafların kararlaştırması ile değil öncelikle kendi iradesi ile olmaktadır. Gönderilenin sorumlu tutulmasının diğer şartını, teslim talebinin dayandığı taşıma sözleşmesinde ya da deniz taşıma senetlerinde bu borçların gönderilen üzerine bırakılması oluşturmaktadır. Dolayısıyla gönderilenin yükün teslimi sözleşmeden ya da deniz taşıma senetlerinden kaynaklanan bu alacakların ödenmesi şartına bağlanmaktadır. Gönderilenin hangi alacaklardan sorumlu olduğu sözleşme şartlarına göre tespit edilmektedir. Bu kapsamda sözleşme kayıtlarının incelenmesi gerekir. Navlun sözleşmesinde gönderilen uygulamada genellikle denizaşırı alıcı olarak karşımıza çıkmaktadır. Dolayısıyla Incoterms uyarınca tarafların kararlaştırdığı teslim şekillerinin ve FIO/FIOST/FILO/LIFO gibi gönderilenin sorumluluğunu genişleten kayıtların incelenmesi önemlidir. Bu kapsamda gönderilenin navlun sözleşmesinden kaynaklanan hangi borç kalemlerinden sorumlu olduğu sözleşme hükümleri ve mevzuat ile ayrıntılı bir şekilde açıklanmıştır. The consignee is defined as a person who requesting the delivery of the cargo at the discharge port by the maritime commercial law. The consignee might be the shipper, as a party of contract of affreightment, or might be a third party of the contract. In the case of the consignee is a third party, the contract of affreightment is characterized as a third-party beneficiary contract in which determined rights and responsibilities are given to this third party by the law makers. This thesis aims to determine the responsibilities of the third-party consignee that arising from the contract of affreightment. With regard to privity of the contract principle, as a rule, parties of a contract do not have right to bind a third party with obligations. On the other hand, the conditions of responsibilities of the third party consignee is regulated in the article 1203 of TCC. With regard to the article, in order for the consignee to be liable under the freight contract, the consignee must first request the delivery of the goods. The demand for the delivery of the goods is considered as the acceptance of the performance in terms of the theory of third party beneficiary contract and as a matter of fact, the consignee do not incur a debt with the parties' decision, but primarily with his own will. The other condition of holding the consignee responsible is the transfer of these debts to the consignee in the contract of affreightment or other transport documents on which the delivery request is based. Therefore, the delivery of the cargo is subject to the payment of these debts arising from the contract or transport documents. The debts of the consignee are determined according to the terms of the contract. In this context, it is necessary to review of the terms of the contract. In practice, the consignee in the contract of affreightment usually appears as a overseas receiver of the sale contract. Therefore, it is important to examine both the delivery methods agreed by the parties with regard to INCOTERMS and clauses that expand the responsibility of the sender, such as FIO/FIOST/FILO/LIFO. In this framework, this study explains in detail the responsibilities of consignee with regard to freight contract provisions and legislations.
Tez N°740401
Keywords: Commercial law; Contracts of affreightments; Deniz hukuku; Droit maritime; Freight; Gönderenin sorumluluğu; Law of the sea; Navlun; Navlun sözleşmeleri; Responsibility; Responsibility attiribution; Senders responsibility; Sorumluluk; Sorumluluk yükleme; Sözleşmeler; Ticaret hukuku

La responsabilité civile du transporteur maritime des hydrocarbures pour faits de pollution - Madani, Ahmed (Université Abou Bekr Belkaid, 2022)
Keywords: Hydrocarbure; Pollution; Responsabilité civile; Transport maritime; Transporteur maritime

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation

Kara eşya taşıma sözleşmelerinde taşıyıcıya teslimin hukuki sonuçları - Sar, Mustafa Seyfullah (İstanbul Ticaret Üniversitesi, 2022)
Mesafe ve sınırların ortadan kalkmasıyla uluslararası ticarette pozitif yönde ivme kazanılmıştır. Bu yolda uluslararası ekonomik ilişkilerin geliştirilmesi amacıyla yapılan anlaşmalar, kurulan örgütler, sağlanan teşvikler ve kaldırılan ithalat vergileri sayesinde, farklı ülkelerdeki firmalar ve bireyler, birbirleriyle daha hızlı bir şekilde alışverişe girmeye başlamış ve bunun sonucunda ticari faaliyetler ülke sınırlarını aşarak küresel boyutlara ulaşmıştır. Bunun sağlanabilmesi için taşıma sektöründe kullanılan araçlar detaylandırılarak daha güçlü hale getirilmiştir. Böylelikle malların dağıtımı daha ekonomik, güvenli ve hızlı bir şekilde gerçekleştirilmektedir. Bunun sonucu olarak taşıma sözleşmelerinin uluslararası ticaretteki yeri de giderek önem kazanmıştır. Öyle ki hakların ve borçların teminatı için sözleşme kaçınılmaz yoldur. Yakın tarihte, uluslararası alanda ticaretin daha kolay ve hızlı hale getirilmesi için yeknesak bir sistem oluşturulması ihtiyacı ortaya çıkmış ve buna binaen ulusal düzenlememiz olan TTK'nın yanında, uluslararası karayolu taşımacılığında, koşulları standardize eden, taşıyıcının sorumluluklarını belirleyen CMR Konvansiyonu oluşturulmuştur. Düzenlenen kurallar doğrultusunda, taşıyıcı eşyayı teslim aldığı andan teslim edinceye kadar zarardan ve kayıptan sorumlu olacaktır. Taşıyıcı, ancak TTK ve CMR'de yer alan genel ve özel kurtuluş karinelerinin varlığının ispatı halinde sorumluluktan muaf olabilecektir. Aksi halde taşıyıcı, meydana gelen zarar veya zayiatın oranı doğrultusunda sorumlu olacak ve buna müteakiben tazminat miktarı belirlenecektir. TTK ve CMR pek çok noktada benzerlik gösterse de bazı yönleriyle keskin farklılıklar mevcuttur. Uluslararası ticaretin bekası için önem oluşturan bu nokta özellikle sorumluluk hususunda hukuki tartışmaları da beraberinde getirmiştir. With the obstacle of distances and borders disappearing, international trade has gained speed in a positive direction. Thanks to deals and agreements that were made, organisations that were built, incentives that were provided, and removal of import taxes in order to improve economic relations with this respect, companies and people in different countries have started to be able merchandise with each other more quickly; consequently, tradal actions have crossed borders of lands and reached global level. For this to happen, vehicles used in the sector of transportation have been developed, thus made stronger and more elaborate. As a result of this, the distribution of goods can be ensured in a more economic, safer, and faster way, and the role of vehicle contracts in international trade has gradually gained importance as contracts are inevitable to ensure and guarantee rights and debts. In recent history, a need to have a uniform system that would enable international trade to be easier and faster was born, and consequently, in addition to our regulations on TTK (Turkish Commercial Code), CMR Convention which standardized conditions and determined the responsibilities that transporters have in international land transportation. According to the regulations, the transporters are responsible for the safety of the goods in case of a damage and loss) from the moment they take them until they deliver them. The transporters can only be exempt from this responsibility in the case that general and specific presumptions of innocence that a place in the law (TTK) and the CMR can be proven. Otherwise, the transporter shall be responsible for compensating for the damage or the loss that occurred and the cost for the indemnity shall be determined. Although TTK and CMR Convention have similarities in many regards, in some ways they are distinctively different from one another. This point which has a critical role in the future of international trade has brought about many juridical discussions, especially ones related to responsibilities.
728226
Keywords: Contracts; Delivery; Eşya taşıma; Goods transportation; Highway Route with International Furniture Removal Agrement; Highway transportation; Kara yolu taşımacılığı; Karayolu ile Uluslararası Eşya Taşıma Sözleşmesi; Obligation to delivery; Sözleşmeler; Teslim borcu; Teslimat; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Las plataformas en línea y el transporte discrecional de viajeros por carretera - Boboc, Silvia (Universitat Jaume I, 2021)
Analiza la ordenación del mercado, la naturaleza jurídica y los interrogantes que desde el Derecho de la competencia plantea la actividad de Uber, Cabify y BlaBlaCar y de los conductores registrados en dichas plataformas. El primer capítulo examina el régimen jurídico del transporte discrecional de viajeros en vehículo de turismo, tanto público como privado, y de la intermediación en el transporte, en la normativa estatal y autonómica. En el segundo capítulo se determina la naturaleza jurídica de la actividad de las plataformas de transporte y de los conductores registrados en las mismas. El tercer capítulo se centra en el análisis de los modelos de negocio de las plataformas desde la óptica de la Ley de competencia desleal y, en concreto, si existe infracción de su artículo 15; mientras que el cuarto y último capítulo examina si las mismas incurren en una conducta colusoria de fijación de precios (art. 101.1 TFUE y art. 1.1 LDC). The doctoral thesis analyses the market regulation, the legal status and the questions that the activity of Uber, Cabify and BlaBlaCar and their registered drivers raise from a Competition Law point of view. The first chapter explores legal regime of public and private occasional transport of passengers by car, and lays out the regulation of transport intermediation activities, at State, autonomic and local level. The second chapter addresses the legal nature of transport platforms activity, as well as that of the drivers registered on said platforms. The third chapter analyses the business models of the platforms from the perspective of Unfair Competition Act, and, in particular, whether they infringe its Article 15; whereas the fourth and last chapter aims to determine if the platforms incur in a collusive price-fixing conduct [Art. 101(1) TFEU and Art. 1(1) DCA].
Keywords: Administració i dret; BlaBlaCar; Economía colaborativa; Negocis; Passager; Taxi; Transport routier; Transporte colaborativo; Uber; VTC; transporte discrecional de viajeros

La dématérialisation des documents de transport maritime de marchandises : étude dans le cadre de la CEMAC - Matchinda, Odette (Université Paris 1, 2021)
La dématérialisation et le droit, un mariage de raison. Les travaux pionniers de Philippe Garo et Albert Dione le démontrent à suffisance. À l’ère du tout numérique l’adaptation du droit en général et du droit maritime en particulier est une condition sine qua none pour la sécurisation des transactions et la confiance dans l’économie numérique. La question relative à la valeur juridique des documents dématérialisés est aujourd’hui résolue par les différents textes de la CNUDCI. Les différentes transpositions légales et la doctrine posent les principes d’équivalence fonctionnelle, de neutralité médiatique et de neutralité technologique. Néanmoins, de nombreuses questions restent en suspens et constituent l’objet de cette thèse. Les documents dématérialisés conservent-ils leurs fonctions juridiques traditionnelles ? Si la réponse est positive, elle reste soumise à la condition que l ’émission, la transmission et ou le transfert du document électronique de transport, titre représentatif de la marchandise, soient encadrés par une méthode fiable permettant d’assurer la confidentialité, l’intégrité et la durabilité du support lors du processus. L’opération semble simple sur le plan conceptuel mais il n’en est rien sur le plan pratique. De nombreuses limites intrinsèques et extrinsèques entravent la mise de la dématérialisation. Cette thèse a pour objet d’y apporter des solutions. De toute évidence, le coût d’opportunité que représente la dématérialisation pour les entreprises dans la zone CEMAC est réel et stratégique. L’adaptation sur le plan législatif est à saluer mais devrait être accompagnée sur le plan pratique par une véritable politique communautaire de maritimisation. Une politique de transport maritime mettant l’accent sur la création d’infrastructures communes permettant d’assurer l’interconnectivité et l’interopérabilité des systèmes. Toute chose à même d’assurer la facilitation de la circulation et le transfert sécurisé des documents dans la chaine de valeur. Une telle politique facilitera aussi le recours dans un proche avenir dans la zone CEMAC, à la technologie Blockchain que nous proposons pour la dématérialisation du connaissement négociable, « véritable serpent de mer » ! Paperless process and the law, a marriage of convenience. The pioneering works of Philippe Garo and Albert Dione demonstrate this enough. In the digital age, adapting law in general and maritime law to electronic commerce is a sine qua non condition for securing transactions and confidence in the digital economy. If the issue relating to the legal status of dematerialized documents is today solved by the various texts of the UNCITRAL, legislation and the doctrine laying down legal principles of functional equivalence, media neutrality and technological neutrality, many questions remain raised and are the basis of this PhD dissertation. Does dematerialized transport documentation preserve their traditional legal functions ? If the answer is positive, it nevertheless remains subject to conditions. The issuing, transmission and or transfer of the electronic transport document, a title representative of the goods, must be supervised a reliable method allowing confidentiality, integrity, and durability of medium to be ensured throughout the process of dematerialization. If on the conceptual level, the operation seems simple, it is not the same on the practical level. Intrinsic and extrinsic limits to the documentary function are as many obstacles to dematerialization that this dissertation tent to resolve. Obviously, the opportunity cost of dematerialization for companies in the CEMAC zone is strategic. The adaptation on the legislative level is to be welcomed but should be accompanied on the practical level by a true community policy of maritime transport. A maritime transport policy emphasizing the creation of common infrastructures to ensure the interconnectivity and interoperability of systems. This has the advantage to ensure the facilitation of circulation and the secure transfer of documents in the full value chain. Such a policy will also facilitate the use soon in the CEMAC zone, of the Blockchain technology that we are proposing for the dematerialization of the negotiable transport document, ''a true sea snake''.
Keywords: Actes juridiques électroniques; Bill of lading; Blockchain; CEMAC; Communication électronique de pièces (droit); Connaissement négociable; Cybercrime; Cybercriminalité; Cyberterrorisme; Data security; Documents électroniques; Droit de la mer; Droit maritime; Dématérialisation; Electronic documents; Maritime transport; State; Transport marchandise; Transport maritime; Échange électronique d'information; États